(untitled) (Revista horizonte, 2013)
Irisin has recently been discovered as a novel hormone secreted as a product of 5-domain fibronectin type III (FNDC5) from skeletal muscle in mice and humans. FNDC5 expression is induced by peroxisome proliferator-activated receptor Î³ (PPARÎ³) and coactivator 1Î± (PGC-1Î±) in skeletal muscle, promoting browning of target adipose tissue by increasing expression of uncoupling protein 1 (UCP 1) increasing thermogenesis and subsequently energy expenditure. Physical exercise induces the expression of ABSTRACT PGC-1Î±, which in muscle induces the release of irisin into the bloodstream. Irisin is studied as a possible therapeutic target for the prevention and treatment of obesity and type 2 diabetes mellitus (DM2), what is still unclear is the role of exercise in its expression. For this review article, only articles indexed in PUBMED were considered, with the combinations IRISNA + EXERCISE, IRISINA + OBESITY. Articles from 2007 to 2013 were reviewed.